(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines one of the interesting topics of Russian literature – the theme of fate. The image of the blizzard-fate is not just a plot element, but a deep philosophical symbol that raises questions about the relationship between man and the elements, free will and forces beyond our control, justice and tragic inevitability.